Journal of Nondestructive Evaluation - Thompson, R. Bruce; Nagy, Peter B.; Meyendorf, Norbert; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Journal of Nondestructive Evaluation provides a forum for the broad range of scientific and engineering activities involved in developing a quantitative nondestructive evaluation (NDE) capability. This interdisciplinary journal publishes papers on the development of new equipment, analyses, and approaches to nondestructive measurements.
Keywords: Mechanics; Vibration; Dynamical systems; Dynamics; Materials science; Solid Mechanics; Characterization and Evaluation of Materials; Vibration, Dynamical Systems, Control; Classical Mechanics